Ear Canal Role and Psychoacoustic Parameters: Loudness, Sharpness, Roughness, and Fluctuation Strength - Hadi Asady; Farhad Forouharmajd; Siamak Pourabdian; Mehdi Jalali; Ali Ahmadi; Fatemeh Ansari; Adrian Fuente (International Journal of Environmental Health Engineering)
Aim: The purpose of this study was to investigate whether psychoacoustic parameters could be significantly influenced by the human ear canal and whether gender played a significant role in these effects. Methods: In this study, sixty participants were enrolled, with an equal distribution of 30 male and 30 female individuals. White and sinusoidal noises at 75, 85, and 95 dB as stimulus sound pressure levels (SSPLs). Psychoacoustic parameters such as loudness, sharpness, roughness, and fluctuation strength were measured both outside (cavum part of the external ear) and inside the right ear of each participant. These measurements were done using a circular-shaped microphone with a 2-mm diameter and Labview software. The duration for each measurement was 10 s. The independent sample t-test and repeated measures ANOVA test were employed for the statistical analysis in this study. The results indicated that the equality of means was rejected at a significance level of P < 0.05. All statistical analyses were conducted using SPSS Version 26. Results: The mean age and standard deviation of all participants were 22.77 ± 2.60 years old. The comparison of psychoacoustic parameters in the exposure to different types of noises at various levels between genders showed no statistically significant differences (all P > 0.05). For both sinusoidal noise and white noise at all three studied SSPLs, the differences in four psychoacoustic parameters between the outer and inner ears of the participants were not statistically significant (all P > 0.05). Conclusion: Based on our findings, it seems that the human ear canal does not have any effect on psychoacoustic parameters, leading us to conclude that the ear canal does not contribute to noise-induced annoyance.